An Analysis of Students’ Errors in Completing Essay HOTS Questions Based On Watson's Criteria Viewed From The Cognitive Style Perspective - Santoso, Teguh; Cholily, Yus Mochamad; Syaifuddin, Mohammad (Universitas Muhammadiyah Mataram, 2021)
This study aimed to determine the students’ errors classified as Field Independent (FI) and Field Dependent (FD) in solving essay HOTS questions based on Watson criteria and to find out the causes of errors experienced by FI and FD types of students in finishing those questions. This was qualitative research which implemented the case study method. This research was carried out at Junior High School 3 Kepanjen Malang of 2019/2020 academic year. Research subjects were determined based on The Group Embedded Figures Test (GEFT) test results. From the test, two students were selected from each type of cognitive style. The applied data collection included tests and interviews. The qualitative data analysis applied four stages: data reduction, data presentation, conclusion, and verification. The results showed that FI students experienced errors in manipulating calculation, false conclusions, incorrect use of mathematical formulas, and false calculation. On the other hand, FD students had errors in mathematical operation signs, erroneous formula writing, irresponsive to problems, errors of manipulating calculation, and not writing mathematical formulas.